Phase equilibria in the Gd–Cr–Ge system at 1070 K - Konyk, M.; Romaka, L.; Stadnyk, Yu.; Romaka, V.V.; Pashkevych, V. (Physics and Chemistry of Solid State, 2021)
The isothermal section of the phase diagram of the Gd–Cr–Ge ternary system was constructed at 1070 K over the whole concentration range using X-ray diffractometry, metallography and electron microprobe (EPM) analysis. Three ternary compounds are realized in the Gd–Cr–Ge system at the temperature of annealing: Gd117Cr52Ge112 (Tb117Fe52Ge112 structure type, space group Fm-3m, Pearson symbol cF1124, a = 2.8971(6) nm), GdCr6Ge6 (SmMn6Sn6 structure type, space group P6/mmm, Pearson symbol hP16, a = 0.51797(2), c = 0.82901(4) nm) and GdCr1-хGe2 (CeNiSi2 structure type, space group Cmcm, Pearson symbol oS16, a = 0.41569(1)-0.41593(8), b = 1.60895(6)-1.60738(3), c = 0.40318(1)-0.40305(8) nm). For the GdCr1-xGe2 compound the homogeneity range was determined (x=0.73 – 0,69).